2015
DOI: 10.4172/2155-6121.1000230
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical Mechanism of Aspirin-Exacerbated Respiratory Disease Based on Recent Investigations of Gene Polymorphisms in Japanese Patients

Abstract: Aspirin-exacerbated respiratory disease (AERD) is characterized by severe asthmatic attack after taking aspirin and/or nonsteroidal anti-inflammatory drugs (NSAIDs). The typical patient with AERD is an adult who develops refractory chronic rhinitis in the third or fourth decade of life. Natural history and clinical features of AERD indicates that during the evaluation of chronic rhinitis persistent bronchial asthma develops, and finally after exposure to NSAID acute respiratory reactions begin to occur. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Some hypotheses are proposed for the role of major histocompatibility complex molecules in drug allergy but not in nonallergic hypersensitivity. 24 Kurosawa et al 25 demonstrated that the frequency of TT/CT genotypes in IL-13 polymorphism -1111 was higher than that of the CC genotype in NSAID-exacerbated asthma disease compared to an aspirin-tolerant group and controls. Interleukin-13 is a cytokine derived from Th2 cells that induces IgE production by B cells and retains a main role in allergicinduced asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Some hypotheses are proposed for the role of major histocompatibility complex molecules in drug allergy but not in nonallergic hypersensitivity. 24 Kurosawa et al 25 demonstrated that the frequency of TT/CT genotypes in IL-13 polymorphism -1111 was higher than that of the CC genotype in NSAID-exacerbated asthma disease compared to an aspirin-tolerant group and controls. Interleukin-13 is a cytokine derived from Th2 cells that induces IgE production by B cells and retains a main role in allergicinduced asthma.…”
Section: Discussionmentioning
confidence: 99%